Classical Wisdom and the In-roots of Modern Advertising - Kumar, Brajesh; Patra, Gouranga (Indian Journal of Marketing, 2010)
Past or present, the core relationship of the businesses has remained the same - the propinquity of interaction between the producers and the consumers within the mechanism of a marketing set up (Calkins, 1905. Longman, 1971. Nevett, 1982). These two are the main players and unless or until this relationship exists and exist mutually beneficial and satisfying, it is doubtful that any such system called: Production-Exchange-Consumption flow sustain itself. Moreover, this relationship over the time has expanded so greately that remoteness in-between the two has been now highly incomprehensible or even intangible. Which substance or system does realy help it to maintain closeness between the said two? In other words, what does make marketing a meaningful engagement? Obviously, it is ADVERTISING. Advertising from its earlier days served to inform, persuade, and remind consumers just as it does today. But it was less pervasive than today because of the limited media and the limited number of goods available for trading (Nons, 1981., Tellis & Ambler, 2008., Phillips, 1992). According to Proctor & Gamble’s chairman: [Think] of advertising and promotion as exercise and recreation. Advertising is exercise. It is some thing you need and it provides long-term benefits, but it is awfully easy to either cut or postpone because there is no immediate penalty for not exercising...(Nevertheless) if you want your brand to be fit, it is good to exercise regularly (Lawrence, 1991). Advertising is the tool that has helped and still helping businesses to bridge the gap of spatial distribution and span of production and final consumption. It is indeed widely dispersed relationship.